2021
DOI: 10.1016/j.rinp.2021.104737
|View full text |Cite
|
Sign up to set email alerts
|

A vigorous study of fractional order COVID-19 model via ABC derivatives

Abstract: The newly arose irresistible sickness known as the Covid illness (COVID-19), is a highly infectious viral disease. This disease caused millions of tainted cases internationally and still represent a disturbing circumstance for the human lives. As of late, numerous mathematical compartmental models have been considered to even more likely comprehend the Covid illness. The greater part of these models depends on integer-order derivatives which cannot catch the fading memory and crossover behavior found in many b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(12 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…Thus, using a fractional derivative to build up a COVID-19 model may address gaps between data and the existing knowledge on the COVID-19 transmission process. However, in all of the existing fractional order models on COVID-19 [25] , [26] , [27] , [28] , [82] , [83] , [84] , [85] , instead of taking fractional derivatives in the force of infection in disease transmission, authors used fractional derivatives only in the population (left-hand side of the system replacing ordinary derivatives with some fractional order derivative), which in general a Markovian process [20] , [21] , [35] , [36] , [38] . Consequently, these models may not be appropriate to study the power law/memory effect in the transmission process of COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, using a fractional derivative to build up a COVID-19 model may address gaps between data and the existing knowledge on the COVID-19 transmission process. However, in all of the existing fractional order models on COVID-19 [25] , [26] , [27] , [28] , [82] , [83] , [84] , [85] , instead of taking fractional derivatives in the force of infection in disease transmission, authors used fractional derivatives only in the population (left-hand side of the system replacing ordinary derivatives with some fractional order derivative), which in general a Markovian process [20] , [21] , [35] , [36] , [38] . Consequently, these models may not be appropriate to study the power law/memory effect in the transmission process of COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study is conducted for the understanding of coronavirus infection and its controls [27]. A mathematical model in non-singular order to investigate the coronavirus infection is considered in [28]. Nonetheless, some studies show that in some conditions, time-varying fractional-order models are able to better demonstrate behavior of systems [40][41][42][43][44][45][46][47].…”
Section: Introductionmentioning
confidence: 99%
“…Using the third layer of COVID-19 cases in Li et al (2021c) , the authors formulated a mathematical model and suggested the results for infection control. A study on the coronavirus infection fractional order is suggested in Li et al (2021d) . The infection of COVID-19 in Nigeria through a mathematical model is explored in Iboi et al (2020a) .…”
Section: Introductionmentioning
confidence: 99%